Predictors of dropout in face-to-face and internet-based cognitive-behavioral therapy for bulimia nervosa in a randomized controlled trial - Watson, Hunna; Zimmer, Benjamin; Kordy, Hans; Moessner, Markus (The international journal of eating disorders, 2017)
Objective We sought to identify predictors and moderators of failure to engage (i.e., pretreatment attrition) and dropout in both Internet-based and traditional face-to-face cognitive-behavioral therapy (CBT) for bulimia nervosa. We also sought to determine if Internet-based treatment reduced failure to engage and dropout. Method Participants (N = 191, 98% female) were randomized to Internet-based CBT (CBT4BN) or traditional face-to-face group CBT (CBTF2F). Sociodemographics, clinical history, eating disorder severity, comorbid psychopathology, health status and quality of life, personality and temperament, and treatment-related factors were investigated as predictors. Results Failure to engage was associated with lower perceived treatment credibility and expectancy (odds ratio [OR] = 0.91, 95% CI: 0.82, 0.97) and body mass index (BMI) (OR = 1.10; 95% CI: 1.03, 1.18). Dropout was predicted by not having a college degree (hazard ratio [HR] = 0.55; 95% CI: 0.37, 0.81), novelty seeking (HR = 1.02; 95% CI: 1.01, 1.03), previous CBT experience (HR = 1.77; 95% CI: 1.16, 2.71), and randomization to the individual's nonpreferred treatment format (HR = 1.95, 95% CI: 1.28, 2.96). Discussion Those most at risk of failure to engage had a higher BMI and perceived treatment as less credible and less likely to succeed. Dropout was associated with less education, higher novelty seeking, previous CBT experience, and a mismatch between preferred and assigned treatment. Contrary to expectations, Internet-based CBT did not reduce failure to engage or dropout. © 2016 Wiley Periodicals, Inc.(Int J Eat Disord 2017; 50:569-577)